Effect of uncertainty in demand and production for manufacturing industries during COVID-19. (9th November 2022) - Sharma, Renu; Singh, Anubhav Pratap; Arora, Ritu; Chauhan, Anand
The demand for personal hygiene products has increased during COVID-19 pandemic outbreaks. It has resulted in the increasing production of hygiene products. During the coronavirus epidemic, globalised and uncertain demand for personal hygiene products creates complicated situations for the manufacturing firms. This article explores the fuzzy model of economic production for hygiene products with uncertainty in demand and production. Due to the rising demand for hygiene products, the demand rate has been set as a linear time function, while the production rate has been taken directly proportional to the rate of demand. Therefore, due to ambiguity or vagueness in demand, this proposed model has considered the triangular fuzzy number with an upper and lower split. The weighted sum method has turned the multi-objective problem into a single objective. The optimisation technique was used to minimise the producer's overall cost under the condition mentioned earlier, and the model is validated numerically.